Investigating the Quality of Diagnostic and Treatment Services Purchased From Specialist Doctors Using the Servqual Model and Giving Solutions - Saeid khayatmoghadam; Azam Babaki Rad; Ali Asghar Zabihi; Ameneh Zabihi (Patient Safety and Quality Improvement Journal)
Introduction:This research aimed to investigate the quality of diagnostic and therapeutic services purchased from specialist doctors using the Servqual model and to provide solutions. Materials and Methods:The opinions of 51 specialists were collected regarding the quality of services provided by doctors using the Servqual standard questionnaire. Then, using the Servqual model, the gap between expectations and perceptions was calculated and ranked based on priority from the largest to the smallest gap. In the following, with the help of the Delphi method, with the cooperation of experts, solutions were collected to improve the dimensions, and after that, the importance of the solutions was determined using the second questionnaire. Results:Gaps in order of priority of reliability, responsiveness, tangibility, assurance, and finally, empathy were determined. Six solutions were determined to improve reliability, 10 to improve responsiveness, 4 to improve physical dimensions (tangible), 9 to improve assurance, and 4 to improve empathy. After ranking the solutions, six solutions that scored lower than the average (3.08) were removed, and  27 solutions were approved. Conclusion:Considering the calculated gap between expectations and perceptions in all dimensions, the following solutions are suggested to reduce the gap; improving the performance of basic insurance organizations, motivating doctors, estimating the price of services based on quality, developing treatment protocols with the help of specialized associations and contracting with doctors by insurance organizations based on the best time for the visit.